Determination of quantum defect for the Rydberg P series of Ca II. (4th October 2019) - Mokhberi, Arezoo; Vogel, Jonas; Andrijauskas, Justas; Bachor, Patrick; Walz, Jochen; Schmidt-Kaler, Ferdinand
Abstract: We present an experimental investigation of the Rydberg 23P1/2 state of single, laser-cooled 40 Ca + ions in a radiofrequency ion trap. Using micromotion sideband spectroscopy on a narrow quadrupole transition, the oscillating electric field at the ion position was precisely characterised, and the modulation of the Rydberg transition due to this field was minimised. From a correlated fit to this P line and previously measured P and F level energies of Ca II, we have determined the ionization energy of 95 751.916(32) cm −1, in agreement with the accepted value, and the quantum defect for the n P1/2 states.